(untitled) (International Journal of Automation and Smart Technology, 2012)
An Ultrathin ( 10 nm) InN ion sensitive field effect transistor (ISFET) with gate regions functionalized with phosphotyrosine (p-Tyr) is proposed to detect calcium ions (Ca2+) in aqueous solution. The ISFET was miniaturized to a chip size of 1.1 mm by 1.5 mm and integrated at the tip of a hypodermic injection needle (18 G) for real-time and continuous monitoring. The sensor shows a current variation ratio of 1.11% with per decade change of Ca2+ and a detection limit of 10-6 M. The response time of 5 sec. reveals its great potential for accomplishing fast detection in chemical and physiological sensing applications. The sensor would be applied in medical diagnosis and used to monitor continuous and real-time variations of Ca2+ levels in human blood in the near future.